Why Are You Reading This? - Beller, Miles (Psychological Perspectives, 2011)
In an age given over to flashing online video games, pulsating virtual reality websites, and quick-cut vids pulsing from cell phones and palm players, why would anyone still bother to read? The ascendancy of the Internet in concert with all manner of electronic diversions has birthed an environment where entertainment seemingly trumps enlightenment. Has the ascendancy of multitasking made obsolete the notion of quietly devoting one's time and mind to lines of print, or has the accelerated pace of technological innovation and marketing exploitation deepened our need to read? Moreover, might reading be the ultimate 'virtual experience,' time and circumstance annihilated, the reader transcending his or own her life and entering a fully realized realm projected by the author? Many outlooks and varied outcomes are provided by what we read, texts ever contexturalizing who we are and who we wish to be. In fact, ancient words continue exerting a gravitational pull on our modern passions and pursuits. Against the instant-on chatter of iPhones and the jabbering blather of Blackberries, the written word continues to be good.